Podział aktów normatywnych na dokumenty - Łachwa, Andrzej (Wydział Prawa i Administracji UAM, 1983)
Functioning of the full text legal data banks consists in providing its users with such fragments of the legal text as might be relevant to resolving definite legal questions. A proper fulfilling of this task is dependent i.e. on the way in which the text in question are subdivided into smaller units denoted by the term documents. The author discusses the problem of the optimal size of such units. Subdividing of the texts into documents is ussually carried out by using manual methods. The author presents a method of subdividing the legal texts into documents automatically. The method refers to what may be called a natural subdivision, i.e. to the subdivision applied by the law-maker. The outlines of an algorithm of the operation of automated subdividing are presented in the form the corresponding flow diagram.
Subdivision of statutory texts into documents